Effect of neuromuscular resistance training on the performance of 5-km runners - Guimarães, Miller P. (Array, 2020)
The study aimed to identify the effect of a neuromuscular resistance training protocol (NRTP) on the performance of 5-km distance runners. This study included 18 male runners (age=29.3±3.2 years, fat percentage=11.3±2.6%, body height=1.77±.04 m, body mass=73.4±4.4 kg, time in 5 km=20.6±2.4 min, training years=4.3±0.7 years). First, volunteers were anthropometrically evaluated, and they performed one-repetition maximum (1RM) 45º leg press (LP) strength test. Second, they performed an incremental protocol in the 45º LP to acquire the electromyographic threshold. Third, they completed a 5-km time trial run (5 km basal). In the fourth session, they performed NRTP in LP. And fifth, the 5-km time trial run was performed at 30 min, 48 h, 96 h, and 144 h post the NRTP intervention. A significant decrease (p≤.05) was observed when baseline values were compared with post 30 min and post 48 h (p=.02 and p=.04, respectively). However, there were significant positive differences in performance (p=.04 for time) when baseline values and post 144 h were analyzed. Therefore, it is concluded that the NRTP can be used by 5-km distance runners to improve their performance with a break of one week between the intervention and test.